1993
DOI: 10.1177/1050651993007003002
|View full text |Cite
|
Sign up to set email alerts
|

Women and the Profession of Technical Writing

Abstract: In the United States, the majority of technical writers and technical writing teachers are women. Their dominance of the profession has several causes, including the attractiveness of writing jobs for women, widespread associations of women and superior writing ability, the social acceptability of women in writing jobs, and occupational segregation. Women's dominance of the profession brings with it the risk of diminishing wages and prestige. To avoid this depreciation of the field, professional associations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The slightly larger number of males in our study seems at odds with the distribution reported for technical writers in the workplace where women outnumber men. For example, in 1992, 62 percent of practitioners were women [24]. Similarly, in a 1995 survey of job satisfaction among members of the Society for Technical Communication, 61 percent of the respondents were women [25].…”
Section: Who Responded?mentioning
confidence: 98%
See 3 more Smart Citations
“…The slightly larger number of males in our study seems at odds with the distribution reported for technical writers in the workplace where women outnumber men. For example, in 1992, 62 percent of practitioners were women [24]. Similarly, in a 1995 survey of job satisfaction among members of the Society for Technical Communication, 61 percent of the respondents were women [25].…”
Section: Who Responded?mentioning
confidence: 98%
“…Similarly, in a 1995 survey of job satisfaction among members of the Society for Technical Communication, 61 percent of the respondents were women [25]. As researchers in this area have noticed, the recent higher proportion of women among practitioners represents a change from the early days of professional writing when men dominated the field [14,15,24,[26][27][28].…”
Section: Who Responded?mentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, more and more arguments, reflections, and critiques have been proposed. For example, Dragga [25] responded to the chart junk debate by arguing that although pictographs are statistically redundant, they are not emotionally redundant. Kennedy et al [39] thought that the binary view of emotion and reason has viewed emotion as irrational and has made emotion intentionally undervalued in data science for a long time.…”
Section: The Debate About Emotion In Visualization Designmentioning
confidence: 99%